Funding International Development Organizations AIIB Yearbook of International Law 2021 - Smith, Christopher; Gao, Xuan; Dollmaier, Thomas (Brill, 2022)
Financing development requires access to financial resources. The AIIB Yearbook of International Law Volume 4 explores the role of international organizations in the development of local capital markets, their legal status under public international law and selected domestic jurisdictions, as well as innovations in resource mobilization and organizational structures. The volume collects insights from distinguished professionals who shed new light on the question of how international development organizations can raise the funds they need to tackle global challenges like the climate crisis, digitalization, or sustainable development. Only by addressing these challenges will international development organizations be able to fully deliver on their development mandate.